Acute Extensor Tenosynovitis due to Disseminated Gonococcal Infection. Issue 9 (September 2019) - Zhou, Joanne Y.; Mittermiller, Paul A.; Nishimoto, Stacie K.; Johannet, Peter; Curtin, Catherine
Abstract : Summary: Infections from Neisseria gonorrhoeae ( N. gonorrhoeae ) are on the rise. Disseminated gonorrhea infections have the unique propensity for causing extensor tenosynovitis of the hand, a topic which has not recently been discussed in the plastic surgery literature. We therefore present a case report of a patient with extensor tenosynovitis of the hand from disseminated gonorrhea and review the literature. A 78-year-old man arrived in the Emergency Department with extensor tenosynovitis of the wrist, dermatitis, and polyarthralgias. He was taken to the operating room for washout of his extensor tendons at the wrist and was subsequently diagnosed with disseminated N. gonorrhoeae and treated with a third-generation cephalosporin. The patient ultimately recovered and regained normal active range of motion of the wrist. With the increasing incidence of N. gonorrhoeae, it is important for hand surgeons to recognize and treat the infection early in its course. This article serves to alert hand surgeons of the unique clinical patterns of N. gonorrhoeae infection, specifically focusing on presentations that include extensor tenosynovitis of the hand.